The Analysis of Low-Cost Pb(II) Adsorbents using Batch Method of Solid-Phase Spectrophotometry - Sulistyo Saputro; Ashadi Ashadi; Lina Mahardiani; Nurma Yunita Indriyanti; Maria Ciptaning Sabdo Kawedhar; Wima Pudya Ajunda (Jurnal Kimia Valensi, 2021)
Heavy metal pollutants contained in wastewater can cause health problems for living things around. Minor to fatal health problems can occur due to heavy metal poisoning, mainly caused by Pb(II) metal.. This study aimed to determine the optimum mass combination of rice husk and zeolite to adsorb Pb(II) metal ions in simulated wastewater, and to determine the sensitivity of the analysis method. This study used Solid Phase Spectrophotometry (SPS) to determine the decrease in Pb(II) metal ion levels after being adsorbed by activated carbon from rice husks and zeolites. This study used an experimental method with simulated wastewater samples containing Pb(II) at several concentrations. Pb(II) adsorption processes by rice husk and natural zeolite used various adsorbents' mass ratios. The adsorbents were characterized by using Fourier-Transform Infra-Red (FTIR) Spectrophotometry. Pb(II) analysis during adsorption processes used a single beam UV-visible Spectrophotometer for Solid-Phase Spectrophotometry. This study indicates that the combination of adsorbent from rice husk and natural zeolite can properly adsorb Pb(II) ions with an adsorption capacity of 0.75 μg g-1 and 0.025 μg L-1 for the LoD of the instrument.